2021
DOI: 10.1108/ecam-07-2020-0547
|View full text |Cite
|
Sign up to set email alerts
|

Public administration strategies that stimulate reverse logistics within the construction industry: a conceptual typology

Abstract: PurposeReverse logistics (RL) is a waste revaluation process aimed at reintroducing once-used materials back into the production cycle. Public administration (PA) plays a strong role in influencing the implementation of RL in the construction industry through policy and laws. While much research identifies PA as an important driver in RL, no research yet describes how this occurs.Design/methodology/approachA systematic literature review was conducted on the theme PA in RL with 93 relevant publications retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…According to this survey, the legislative drive aids in the improvement of waste management to boost company performance. This study's findings are consistent with [58,60,61], which suggested that businesses are affected by regulatory and environmental legislation. The chi-square statistic would seem in the value column right portion of "Pearson chisquare" in the result shown in Table 14.…”
supporting
confidence: 86%
“…According to this survey, the legislative drive aids in the improvement of waste management to boost company performance. This study's findings are consistent with [58,60,61], which suggested that businesses are affected by regulatory and environmental legislation. The chi-square statistic would seem in the value column right portion of "Pearson chisquare" in the result shown in Table 14.…”
supporting
confidence: 86%
“…This result corroborates Huang et al (2018)'s findings that regulatory bodies' monitoring plays a significant role in promoting waste management in China. Brandão et al (2021a) posited that government incentivizing schemes advocate controlling illegal dumping while encouraging RL processes. The current study found that, as custodian, the state government organizations incentivize the RLSC of DW and inform the internal stakeholders of new technologies and infrastructure to enhance their operations' quality.…”
Section: Discussionmentioning
confidence: 99%
“…The internal stakeholders in the RLSC always try to minimize their cost of operations rather than following QA practices to yield a maximum waste recovery (Ghisellini et al , 2018). Within this context, Brandão et al (2021a) mentioned that a forceful and stringent influence should be available for the CI actors to change their attitudes and behaviors toward adopting QA practices in waste management. For instance, in the absence of strict regulatory mandates, the study found that the external stakeholders were only induced to follow QA practices due to aggressive fiscal triggers like landfill levy, gate fees and market demand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations